Optimisation of energy consumption and greenhouse gases emissions of nickel in electric vehicle (EV) batteries - See, Choon Ming (2022)
The sales of electric vehicles have skyrocketed in recent years due to the high demand as gas prices spike coupled with regulations set by the governments around the world. At the heart of the electric vehicle is the lithium-ion battery where the vehicle draws its source of energy for propulsion. Despite its sustainability compared to conventional fossil fuels, the manufacturing process of the battery is always a concern as the processes consume a lot of energy and emit high amounts of greenhouse gases as well. This work analyses the main source of energy consumption and emissions in the manufacturing step by way of Life Cycle Assessment study. Optimisation pathways are subsequently proposed to reduce energy consumption and greenhouse gas emissions. Several models were built and compared based on battery type, country grid, and source of nickel ore. After model was built and analysed, it was found that drying process, N-Methyl-2-pyrrolidone (NMP) solvent drying process, dry room operation and nickel use are the root cause to high emissions and energy consumption. Hence, alternatives were proposed to improve the situation such as the Tesla heat pump for NMP recovery, Cotes dry room technology, replacement of complete renewable energy source, and dry cathode to replace wet slurry cathode. Optimization using Tesla heat pump with our model showed a lower percentage reduction of 2.82 % for GWP and 1.68 % for PED, followed by Cotes’ dry room technology reducing GWP by 9.27 % and PED by 3.48 % compared to the conventional desiccant dry room system. Next, dry cathode improved the cell production by reducing the GWP by 25.29 % and PED by 10.62 %. The conversion of non-renewable energy natural gas to solar panel renewable energy as energy source can reduce up to 227.67 % of GWP and 109.60 % of PED. Our models also show that impact to the environment can be reduced by replacing non-renewable energy with renewable energy as the energy source and using dry cathode technology as alternative technology to replace wet slurry cathode.